IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS 3 DI SDN KARANGROTO 02 - Dianita Ayu Permatasari Permatasari; Rida Fironika Kusumadewi; Nuhyal Ulia (STKIP Subang, 2025)
The relatively low achievement of students in the IPAS subject remains an issue that needs to be addressed through the implementation of effective teaching approaches. This study aims to evaluate the effectiveness of differentiated instruction based on learning styles in improving the academic performance of third-grade students at SDN Karangroto 02. A quantitative approach was employed using a quasi-experimental method with a Nonequivalent Control Group Design. Two classes participated in the study: the experimental group, which received differentiated instruction, and the control group, which was taught using conventional methods. Data were collected through pretests and posttests, and analyzed using descriptive and inferential statistics. The results indicated that the experimental class demonstrated a more substantial improvement in learning outcomes compared to the control class. The N-Gain score for the experimental group was 0.32, categorized as moderate, while the control group only achieved a score of 0.12, which falls under the low category. Furthermore, t-test results revealed a statistically significant difference between the two groups. Therefore, it can be concluded that differentiated instruction is effective in enhancing student learning outcomes in the IPAS subject.